Coculture techniques for modeling retinal development and disease, and enabling regenerative medicine. (7th August 2020) - Ghareeb, Ali E.; Lako, Majlinda; Steel, David H.
Abstract: Stem cell-derived retinal organoids offer the opportunity to cure retinal degeneration of wide-ranging etiology either through the study of in vitro models or the generation of tissue for transplantation. However, despite much work in animals and several human pilot studies, satisfactory therapies have not been developed. Two major challenges for retinal regenerative medicine are (a) physical cell-cell interactions, which are critical to graft function, are not formed and (b) the host environment does not provide suitable queues for development. Several strategies offer to improve the delivery, integration, maturation, and functionality of cell transplantation. These include minimally invasive delivery, biocompatible material vehicles, retinal cell sheets, and optogenetics. Optimizing several variables in animal models is practically difficult, limited by anatomical and disease pathology which is often different to humans, and faces regulatory and ethical challenges. High-throughput methods are needed to experimentally optimize these variables. Retinal organoids will be important to the success of these models. In their current state, they do not incorporate a representative retinal pigment epithelium (RPE)-photoreceptor interface nor vascular elements, which influence the neural retina phenotype directly and are known to be dysfunctional in common retinal diseases such as age-related macular degeneration. Advanced coculture techniques, which emulate the RPE-photoreceptor and RPE-Bruch's-choriocapillaris interactions, can incorporate disease-specific, human retinal organoids and overcome these drawbacks. Herein, we review retinal coculture models of the neural retina, RPE, and choriocapillaris. We delineate the scientific need for such systems in the study of retinal organogenesis, disease modeling, and the optimization of regenerative cell therapies for retinal degeneration. : Abstract : Neural retina, retinal pigment epithelium, and choriocapillaris are highly interdependent and therefore coculture techniques are required to understand normal development and disease. Furthermore, coculture techniques will enable the optimization of regenerative therapies and the development of transplantable multitissue sheets.